The global political economy of trade protectionism and liberalization : trade reform and economic adjustment in textiles and clothing - Heron, Tony , 1971- (Abingdon, Oxon : Routledge, 2012)
Examines the social, political and economic impacts of trade, paying attention to the textiles and clothing sector with respect to developing countries. This book is suitable for those studying and researching international and comparative political economy, developing area studies, economics, law and geography
Includes bibliographical references (p. [171]-181) and index
Keywords: Clothing trade -- Government policy; Commercial policy; Free trade; International trade; Protectionism; Textile industry -- Government policy